2017
DOI: 10.1021/acs.jchemed.6b00915
|View full text |Cite
|
Sign up to set email alerts
|

Developing Students’ Scientific Writing and Presentation Skills through Argument Driven Inquiry: An Exploratory Study

Abstract: In this study, we employed a new instructional model that helps students develop scientific writing and presentation skills. Argument-driven inquiry (ADI) is one of the most novel instructional models that emphasizes the role of argumentation and inquiry in science education equally. This is an exploratory study where five ADI lab activities take place with a group of students guided by their classroom teacher. The main aim of this study was to investigate the effect of laboratory instruction that was designed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 24 publications
1
26
0
1
Order By: Relevance
“…This result further suggesting that the more argument-driven strategies are implemented, the more mastered of students' skill in generating scientific arguments (Figure 4.). This finding supported the previous research which is finding that the implementation of Argument-driven inquiry (ADI) model has succeeded to improve students' writing and presentation skills [16]. The current result shows that student ability in writing well-developed over time.…”
Section: B Student' Skill In Generating Writing Argumentsupporting
confidence: 90%
“…This result further suggesting that the more argument-driven strategies are implemented, the more mastered of students' skill in generating scientific arguments (Figure 4.). This finding supported the previous research which is finding that the implementation of Argument-driven inquiry (ADI) model has succeeded to improve students' writing and presentation skills [16]. The current result shows that student ability in writing well-developed over time.…”
Section: B Student' Skill In Generating Writing Argumentsupporting
confidence: 90%
“…In the literature, the potential use of ADI was found to improve students' conceptual understanding (Celep, 2015;Celik & Kilic, 2014;Enderle, Grooms, & Sampson, 2013;Ping, Halim, & Osman, 2020;Myers, 2015) and argumentation skills (Cetin & Eymur, 2017;Fadillah & Deta, 2020;Kadayifci & Celik, 2016;Myers, 2015;Ping et al, 2020). In addition, some studies reported the effectiveness of ADI in developing students' academic achievement (Demircioglu & Ucar, 2015) and scientific process skills (Eymur, 2018;Kadayifci & Celik, 2016;Ping et al, 2020).…”
Section: Argument-driven Inquirymentioning
confidence: 99%
“…In the literature, several empirical studies in different disciplines of science have extensively examined and reported the efficacy of ADI in improving students' conceptual understanding (Myers, 2015;Celep, 2015;Celik & Kilic, 2014;Walker, Sampson, Grooms, Anderson, & Zimmerman, 2012;Enderle, Grooms, & Sampson, 2013). Previous studies showed that ADI can also help foster students' argumentation skills in science (Çetin & Eymur, 2017;Kadayifci & Celik, 2016;Myers, 2015;Walker, Sampson, Grooms, Anderson, & Zimmerman, 2012;Demircioglua & Ucarb, 2015;Celik & Kilic, 2014). To cite an example, Enderle, Grooms, and Sampson (2013) conducted a comparative case study on the impact of ADI on students' science proficiency over traditional laboratory instruction.…”
Section: Argument-driven Inquirymentioning
confidence: 99%